The Dynamics of Sustainable Development in Rurban Area (Case Study in Mejobo Village, Mejobo District, Kudus Regency) - Marthin Oktovianus Nggili; Sugiono Soetomo (The Indonesian Journal of Planning and Development, 2018)
Mejobo Village was located in the Southern part of Kudus Regency, is a strategic area for the development of industrial activities. The growth of small and household, industrial activities in agricultural areas in Mejobo Village has led to the formation of the rural-urban areas (rurban). This study aims to describe the dynamics of sustainable development in rurban areas in Mejobo Village alongside the development of the industrial sector in agricultural areas. The research method being used in this study is quantitative, where data are collected through questioner, conducted observation, semi-structured interview, and obtained documents that are relevant to the investigation. The research shows that in Mejobo Village proves of sustainable development can be found within the economic activities; productivity of industrial activities; community activities and the availability of environmental facilities and infrastructure. Through this study, it can be concluded that the change from rural to rural-urban areas due to the development of small industries and households’ industries in Mejobo Village has been sustainable, with the need for continuous attention towards the productivity of the agricultural areas, so that it remains as the basis of local economic development.